2011
DOI: 10.1002/hbm.21072
|View full text |Cite
|
Sign up to set email alerts
|

Constrained principal component analysis reveals functionally connected load‐dependent networks involved in multiple stages of working memory

Abstract: Constrained principal component analysis (CPCA) with a finite impulse response (FIR) basis set was used to reveal functionally connected networks and their temporal progression over a multistage verbal working memory trial in which memory load was varied. Four components were extracted, and all showed statistically significant sensitivity to the memory load manipulation. Additionally, two of the four components sustained this peak activity, both for approximately 3 s (Components 1 and 4). The functional networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 47 publications
(54 reference statements)
6
74
2
Order By: Relevance
“…However, in contrast to previous nonsocial studies of working memory, we also observed load-dependent increases in mentalizing regions including dorsomedial prefrontal cortex (DMPFC) (−12, 38, 49) extending into anterior paracingulate cortex (DMPFC/APC) ( 12,29,31), precuneus/posterior cingulate cortex (PC/PCC) (0, −61, 46), and TPJ (−42, −70, 40) ( Fig. 2 and Table S2).…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…However, in contrast to previous nonsocial studies of working memory, we also observed load-dependent increases in mentalizing regions including dorsomedial prefrontal cortex (DMPFC) (−12, 38, 49) extending into anterior paracingulate cortex (DMPFC/APC) ( 12,29,31), precuneus/posterior cingulate cortex (PC/PCC) (0, −61, 46), and TPJ (−42, −70, 40) ( Fig. 2 and Table S2).…”
Section: Resultscontrasting
confidence: 98%
“…Our results indicate that at least some components of the mentalizing network are capacity limited and increase activity with effort and social load level. Such findings simultaneously inform and create possible hypotheses for research in social neuroscience, as well as research on the default-mode system, which previously characterized this network as interfering with, rather than supporting, effortful cognition (11,12).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations